On the borderline between art. and philosophy the status and structure of the work of art. As seen by Mieczysław Porębski - Kołek, Bożena (Folia Philosophica, 2003)
The present article consists in a detailed analysis of Mieczysław Porębski’s, nowhere so far published, comprehensive stance towards the work of art. His approach, presented here, is called iconic, and is characterised by the treatment of a work of art as a picture, constituting an element of the general iconosphere, and a response to the expectations created by the time honoured way of treating works of art as texts, that is from a semiotic point of view. The article shows the way the work of art is structured, and analyses its subsequent layers. Three ways of understanding the work of art as an image are distinguished: in the sense of projecting the world of represented objects, in the sense of a complex trace betokening the underlying zone of actions and motivations, and in the sense of its own representative structure and the systemic context of that structure. The author strives also to define the essence of the work of art with reference to its spatial and temporal dimensions seen as its attributes.